Probing the morphological influence on solid electrolyte interphase and impedance response in intercalation electrodes. Issue 15 (21st April 2015) - Chen, Chien-Fan; Mukherjee, Partha P.
<x xml:space="preserve">Abstract</x> The microstructure-aware impedance model allows for the impact of active material morphology on the SEI formation and corresponding impedance response.